PERKEMBANGAN INTELEGENSI DAN PERKEMBANGAN FISIK PADA REMAJA - NurAyu Winingsih; Meilan Matiti; Frezy Paputungan (Jurnal Ilmu Pendidikan dan Budaya, 2023)
Adolescent growth and development is an important period in a person's life. During this period, adolescents experience significant changes in various aspects of life, including the development of intelligence and physical growth. Adolescent intelligence includes cognitive, emotional, and social aspects. Intelligence is an internal factor that is influenced by heredity, but the environment also plays an important role in manifesting intelligence potential. The growth of adolescent intelligence affects their ability to solve problems and make decisions. This study uses qualitative research methods to understand the development of intelligence and physical development of adolescents. This method allows for a deep understanding of individual experiences and thoughts. Intelligence growth is influenced by innate, environmental, maturity, formation, interest, and freedom factors. Physical development is influenced by family factors, nutrition, emotional disturbances, and exercise. Development, Personal Life, Individual, Adolescence. intelligence development and physical development in adolescents have a relationship that influences each other. The process of physical development can affect the development of intelligence, while optimal intelligence development can also support healthy physical development. It is important for individual adolescents to receive good mental stimulation, a supportive environment, and adequate physical and health care to support their overall development..